2002
DOI: 10.1007/s11738-002-0057-x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis of Gentiana genus III. Characterization of three-year-old embryogenic suspensions of G. pannonica originated from various seedling explants

Abstract: Experiments were carried out with three-year-old embryogenie suspension culture of Gentiana pannonica Scop. The initial explant for the suspension determinated both the embryogenic character and embryo production. Cultures were initiated by culture of hypocotyl, cotyledon and root explants on MS (Mnrashige and Skoog 1962) medium supplemented with 1.0 mg.l-Kinetin and 0.5 mg.l 2,4-D, later transferred and main-1 tained in liquid MS medium with 1.0 mg-l-Dicamba, 0.1 mg-l-I NAA, 2.0 mg-1-1 BAP and 80.0 mg-l-r AS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
(17 reference statements)
0
18
0
Order By: Relevance
“…As evident in the current study, the ends of vascular strands located at the four corners of the groups of vascular bundles potentially provide sites of connection for the vascular traces of the adventitious bud primordia that originated in the periderm (Figs 4Á5). With tissue within the transition zone in other gentian species being capable of greater bud initiation in vitro than the shoot (Mikula et al 2002(Mikula et al , 2005, this region of the seedling appears to offer ideal conditions for the initiation of adventitious buds. Hence, based on the structure of the different species of gentian seedlings investigated during the current study and as evident in other herbaceous and woody perennials, it is concluded that in gentians the transition zone is the site for formation of bud clusters under natural conditions.…”
Section: Are Crown Buds Adventitious or Axillary?mentioning
confidence: 99%
“…As evident in the current study, the ends of vascular strands located at the four corners of the groups of vascular bundles potentially provide sites of connection for the vascular traces of the adventitious bud primordia that originated in the periderm (Figs 4Á5). With tissue within the transition zone in other gentian species being capable of greater bud initiation in vitro than the shoot (Mikula et al 2002(Mikula et al , 2005, this region of the seedling appears to offer ideal conditions for the initiation of adventitious buds. Hence, based on the structure of the different species of gentian seedlings investigated during the current study and as evident in other herbaceous and woody perennials, it is concluded that in gentians the transition zone is the site for formation of bud clusters under natural conditions.…”
Section: Are Crown Buds Adventitious or Axillary?mentioning
confidence: 99%
“…Gentiana genus belonging to Gentianaceae includes 361 species spread all over the world (Mikula et al 2002). In Turkish flora it is represented by 13 taxa in total, including 9 species and 4 subspecies (Davis 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, it transpired that CPM1 medium is the most appropriate for callus proliferation of G. kurroo and is almost as good as CPM3 for G. tibetica. CPM3 medium containing 1.0 mg l -1 dicamba, 2.0 mg l -1 BAP, 0.1 mg l -1 NAA and 80 mg l -1 adenine sulfate is an universal medium typically used for the initiation and maintenance of cell suspension cultures of G. tibetica, G. cruciata and G. pannonica (Mikuła et al 2002(Mikuła et al , 2005.…”
Section: The Influence Of Culture Conditions On Callus Proliferation mentioning
confidence: 99%
“…Recently, we succeeded in regenerating plants from leaf mesophyll protoplasts of G. decumbens by indirect somatic embryogenesis (Tomiczak et al 2015). PRM3 medium containing 1.0 mg l -1 kinetin, 0.5 mg l -1 GA 3 , 80 mg l -1 adenine sulfate, which led to the formation of somatic embryos from protoplast-derived tissues of G. decumbens, was the same medium as was widely used for the induction of somatic embryogenesis from callus and cell suspensions of G. pannonica, G. cruciata, G. tibetica (Mikuła and Rybczyński 2001;Mikuła et al 2002), and G. kurroo (Fiuk and Rybczyński 2008a), as well as from protoplasts of G. kurroo cell suspensions (Fiuk and Rybczyński 2007). The greatest number of somatic embryos regenerated from mesophyll protoplast-derived callus of G. tibetica and G. kurroo was also achieved by using this medium.…”
Section: The Influence Of Culture Conditions On Callus Proliferation mentioning
confidence: 99%